IDNLearn.com is your trusted platform for finding reliable answers. Get the information you need from our community of experts who provide accurate and thorough answers to all your questions.
Sagot :
To solve the equation [tex]\((4x - 16)^{\frac{1}{2}} = 36\)[/tex], we need to go through the following steps:
1. Square both sides of the equation to eliminate the square root:
[tex]\[ \left( (4x - 16)^{\frac{1}{2}} \right)^2 = 36^2 \][/tex]
This simplifies to:
[tex]\[ 4x - 16 = 1296 \][/tex]
2. Isolate the term involving [tex]\(x\)[/tex]:
To do this, add 16 to both sides of the equation:
[tex]\[ 4x - 16 + 16 = 1296 + 16 \][/tex]
Which simplifies to:
[tex]\[ 4x = 1312 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
Divide both sides by 4:
[tex]\[ x = \frac{1312}{4} \][/tex]
Simplifying the division:
[tex]\[ x = 328 \][/tex]
4. Verify the solution:
Substitute [tex]\(x = 328\)[/tex] back into the original equation to ensure both sides are equal:
[tex]\[ (4 \cdot 328 - 16)^{\frac{1}{2}} = 36 \][/tex]
Simplifying inside the parentheses:
[tex]\[ (1312 - 16)^{\frac{1}{2}} = 36 \][/tex]
Which becomes:
[tex]\[ (1296)^{\frac{1}{2}} = 36 \][/tex]
Since [tex]\(1296\)[/tex] is the square of [tex]\(36\)[/tex] ([tex]\(36^2 = 1296\)[/tex]), taking the square root of [tex]\(1296\)[/tex] indeed gives [tex]\(36\)[/tex]:
[tex]\[ 36 = 36 \][/tex]
Thus, the solution to the equation [tex]\((4x - 16)^{\frac{1}{2}} = 36\)[/tex] is [tex]\(x = 328\)[/tex].
Therefore, the correct answer is:
[tex]\[ x = 328 \][/tex]
1. Square both sides of the equation to eliminate the square root:
[tex]\[ \left( (4x - 16)^{\frac{1}{2}} \right)^2 = 36^2 \][/tex]
This simplifies to:
[tex]\[ 4x - 16 = 1296 \][/tex]
2. Isolate the term involving [tex]\(x\)[/tex]:
To do this, add 16 to both sides of the equation:
[tex]\[ 4x - 16 + 16 = 1296 + 16 \][/tex]
Which simplifies to:
[tex]\[ 4x = 1312 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
Divide both sides by 4:
[tex]\[ x = \frac{1312}{4} \][/tex]
Simplifying the division:
[tex]\[ x = 328 \][/tex]
4. Verify the solution:
Substitute [tex]\(x = 328\)[/tex] back into the original equation to ensure both sides are equal:
[tex]\[ (4 \cdot 328 - 16)^{\frac{1}{2}} = 36 \][/tex]
Simplifying inside the parentheses:
[tex]\[ (1312 - 16)^{\frac{1}{2}} = 36 \][/tex]
Which becomes:
[tex]\[ (1296)^{\frac{1}{2}} = 36 \][/tex]
Since [tex]\(1296\)[/tex] is the square of [tex]\(36\)[/tex] ([tex]\(36^2 = 1296\)[/tex]), taking the square root of [tex]\(1296\)[/tex] indeed gives [tex]\(36\)[/tex]:
[tex]\[ 36 = 36 \][/tex]
Thus, the solution to the equation [tex]\((4x - 16)^{\frac{1}{2}} = 36\)[/tex] is [tex]\(x = 328\)[/tex].
Therefore, the correct answer is:
[tex]\[ x = 328 \][/tex]
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Thank you for trusting IDNLearn.com. We’re dedicated to providing accurate answers, so visit us again for more solutions.